A comparative study of three chemometrics methods combined with excitation–emission matrix fluorescence for quantification of the bioactive compounds aesculin and aesculetin in Cortex Fraxini - Li, Ze Ying; Li, Xin Kang; Lin, Yuan; Feng, Na; Zhang, Xiang-Zhi; Li, Qing-Lin; Li, Bao Qiong (Frontiers in Chemistry, 2022)
Cortex Faxini is an important traditional Chinese herbal medicine with various medical functions. Aesculin and aesculetin are the main effective components of Cortex Faxini, and the fluorescence signals of the two compounds have a high degree of overlap with each other, making the quantitative analysis difficult based on conventional analytical methods. In the present study, different chemometrics methods including lasso regression (LAR), interval partial least squares (iPLS), and multidimensional partial least squares (N-PLS) methods were employed and combined with excitation-emission matrix(EEM) fluorescence for the accurate quantification of aesculin and aesculetin in Cortex Faxini samples. Consequently, the most satisfactory results with the correlation coefficient of calibration (Rc) and prediction (Rp) values were higher than 0.9972 and 0.9962, respectively, root mean squared errors for calibration (RMSEC) and prediction (RMSEP) values lower than 0.0304 and 0.1165, respectively, and the recovery values were in the range of 83.32%-104.62% were obtained by N-PLS method based on the EEM spectra without scatterings. The obtained credible models indicated that the N-PLS method combined EEM spectra has the advantages of green, low-cost and accurate can be used as a good strategy for the determination of active compounds in complex samples. In order to further confirm the accuracy of the obtained results, the same samples were analyzed by the recognized UPLC method.